Poverty risk trend in Slovakia: Changes in time and space - Michálek, Anton (Quaestiones Geographicae, 2017)
Poverty is a serious problem in Slovakia, and it is concentrated in a few regions. The aim of this paper is to capture the spatial differences in poverty in order to identify the poorest districts and to point to the change in the development of poverty in regions during one decade (2001–2011). It was an important period, because it was when Slovakia joined the EU (2004) and the euro zone (2009), that the financial crisis appeared. Our approach to the topic of poverty is based on an aggregated poverty indicator. The indicator reflects three kinds of risks and a broad spectrum of poverty aspects.